New training program for the new requirements of combat of tactical athletes (2022)
Actual theaters of operations are complex contexts where soldiers must face different situations, such as symmetrical, asymmetrical, or close quarter combat. The requirements of the actual battlefield are different to the traditional conditioning military training. This new changing scenario produces an activation of the innate fight or flight defense mechanisms with large activations of the anaerobic metabolic pathways and the sympathetic autonomic nervous system. In these scenarios, the anaerobic, aerobic, and strength demands are so specific and the time to improve all training demands in the units is limited. We propose a new training periodization for the military population based on the latest research into the psychophysiological response of soldiers in actual theaters of operations (actual military missions) and actual civilian models of training and periodization to develop a specific, easy, and reliable periodization model for actual tactical athletes. This training intervention was developed in order to improve operational training according to the demands of actual theaters of operations, based on recent research in military and civilian populations. We tried to conduct a proposal that is easy to apply, with minimal use of material different to what could be found in a military base and that could be implemented in a short period of time.